The moral value of the anthology of short stories Senyum Karyamin by Ahmad Tohari and its relevance in literary learning in high school - Susilo, Jimat; Putri , Ilmiyanti Rahayu; Astriyani, Astriyani; Salsabila, Wanda Ayu; Fauzi, Nurul Atikah (Universitas Ahmad Dahlan, 2025)
This study examines the representation of moral values in the Anthology of Short Stories Senyum Karyamin by Ahmad Tohari and its relevance in literary learning in high school. Through a qualitative-descriptive research method with content analysis techniques, the researcher found four main categories of moral values, namely values related to God, self, the social environment, and nature, with a strong dominance in social aspects. This tendency shows the author's ideological intention in framing social reality morally. The results of the study show that these values are relevant for the formation of students' character, especially in the aspects of spirituality, personal responsibility, interpersonal communication, and environmental concern. Therefore, this anthology is worthy of being used as a teaching resource in strengthening value-based literary literacy in grade XI of high school.